2014
DOI: 10.1002/app.41759
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing performance of optical sensor through the introduction of polystyrene and porous structures

Abstract: Simple and promising approaches for developing high‐performance Fe3+ sensors were proposed. Polyvinyl chloride (PVC) membrane containing pyrene as a fluorescent indicator was prepared via solvent‐cast method. Upon immersion into 1.0 mM Fe3+ solution, the fluorescence emission of the membrane decreased with the ratio of fluorescence intensities before and after (F0/F) immersion of 1.25. The sensitivity enhancement was achieved through the introduction of polystyrene (PS) onto PVC and the introduction of porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, the sensing performance was slightly improved in the presence of PS. PS fibres and PS-co-PMMA fibres exhibited higher quenching efficiencies than PMMA-PVC terpolymer fibres, possibly due to the π − π stacking between pyrene and the phenyl groups of PS 3,6 . Although PS fibres was expected to provide higher sensing performance than PS-co-PMMA fibres due to a higher PS content, the performance was likely offset by the larger fibre size.…”
Section: Sensing Performance Towards Dnt Fibresmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the sensing performance was slightly improved in the presence of PS. PS fibres and PS-co-PMMA fibres exhibited higher quenching efficiencies than PMMA-PVC terpolymer fibres, possibly due to the π − π stacking between pyrene and the phenyl groups of PS 3,6 . Although PS fibres was expected to provide higher sensing performance than PS-co-PMMA fibres due to a higher PS content, the performance was likely offset by the larger fibre size.…”
Section: Sensing Performance Towards Dnt Fibresmentioning
confidence: 98%
“…The improvement in fluorescence quenching sensitivity with secondary porous structures was observed, and this could be attributed to the increased surface area, which facilitated quenchers to diffuse into nanofibres. In addition, our group recently reported the enhancement in Fe 3+ detection using pyrene as a chromophore through the introduction of polystyrene and porous structures 6 . In this work, pyrene-doped fibres from three different polymer solutions, that is, poly(methyl methacrylate) (PMMA) and poly(vinyl chloride-co-vinyl acetate-covinyl alcohol) (PVC terpolymer), polystyrene (PS), and poly(styrene-co-methyl methacrylate) (PS-co-PMMA), were prepared via electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent polymeric microspheres with controlled particle size, high photostability, tunable emission properties, and thermal stability make them suitable as micro- or nanosensors for analysis and device fabrication. , For instance, M. A. Winnik et al reported lanthanide metal-encoded polystyrene microbeads where the postfunctionalization of fluorescent microbeads with analyte was applied for highly multiplexed bioassay . Fluorescent microbeads are usually synthesized by physical entrapment of dye in a polymer matrix such as poly­(methyl methacrylate), polysilane, polyvinyl chloride, polystyrene, and cellulose acetate . Research from the group of D. R. Walt et al and O. S. Wolfbeis et al have demonstrated the applications of fluorescent microspheres for different types of sensors like high density sensing and suspension array, bar-coding, and in optical fiber sensors as an artificial nose. However, dye leakage and low photostability limits the utility of the fluorophore entrapped polymer in applications involving long-time fluorescence monitoring. , …”
Section: Introductionmentioning
confidence: 99%
“…Winnik et al reported lanthanide metal-encoded polystyrene microbeads where the postfunctionalization of fluorescent microbeads with analyte was applied for highly multiplexed bioassay. 14 Fluorescent microbeads are usually synthesized by physical entrapment of dye in a polymer matrix such as poly(methyl methacrylate), 15 polysilane, 16 polyvinyl chloride, polystyrene, 17 and cellulose acetate. 18 Research from the group of sensors like high density sensing and suspension array, barcoding, and in optical fiber sensors as an artificial nose.…”
Section: ■ Introductionmentioning
confidence: 99%
“…First, to produce a polymer membrane using the solvent casting method, a polymer solution is poured into a casting mold, the solvent of the polymer is vaporized, and a polymer membrane is obtained. Through solvent casting, Wang et al fabricated a cross-linked polyvinyl alcohol and tetramethylpiperidine-1-oxy radical-oxidized cellulose nanofibril membrane [14], and Panawong et al developed an optical sensor to detect Fe 3+ using the solvent casting method with polyvinyl chloride solution and pyrene [15]. In addition, Kwon et al made an ionic polymer actuator using on anion-conducting methylated poly[(1-(4, 4_-diphenylether)-5-oxybenzimidazole)benzimidazole] membrane [16].…”
Section: Introductionmentioning
confidence: 99%